Carbon Loss Pathways in Degraded Peatlands: New Insights From Radiocarbon Measurements of Peatland Waters - Jon Walker (Journal of Geophysical Research: Biogeosciences, 2022)
Peatland carbon stores are under widespread anthropogenic pressure, resulting in degradation and carbon loss. This paper presents DO14C (Dissolved Organic Carbon) dates from waters draining two eroded blanket peatland catchments in the UK. Both catchments are characterized by severe gully erosion but one additionally has extensive surface erosion on unvegetated surfaces. DO14C values ranged from 104.3 to 88.6 percent modern (present to 976 Before Present). The oldest DOC dates came from the catchment characterized by both gully and surface erosion and are among the oldest reported from waters draining temperate peatlands. Together with peat age-depth data from across the peatland landscape, the DO14C ages identify where in the peat profile carbon loss is occurring. Source depths were compared with modeled water table data indicating that in the catchment where gully erosion alone dominated, mean water table was a key control on depth of DOC production. In the system exhibiting both gully erosion and surface erosion, DOC ages were younger than expected from the age of surficial peats and measured water tables. This may indicate either that the old organic matter exposed at the surface by erosion is less labile or that there are modifications of hydrological flow pathways. Our data indicate that eroded peatlands are losing carbon from depth, and that erosion form may be a control on carbon loss. Our approach uses point measurements of DO14C to indicate DOC source depths and has the potential to act as an indicator of peatland function in degraded and restored systems.